Two Factor Authentication Berbasis SMS pada Layanan Single Sign-On Universitas Mataram: SMS Based Two Factor Authentication in Mataram University’s Single Sign-On Service - Ahmad Zafrullah Mardiansyah; Ariyan Zubaidi; I Gde Putu Wirarama Wedaswhara W; Andy Hidayat Jatmika (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
Security is an important part of electronic transactions. Information systems at Mataram University are generally using the conventional username and password fields to authenticate the user (Single Factor Authentication - SFA). The SFA method is vulnerable to brute force attacks, especially to the Single Sign-On (SSO) service. To prevent brute force attacks, this study proposes an implementation of SMS-based Two Factor Authentication (TFA) toward SSO. This study found that the tests carried out by analyzing the simulation of brute force attacks, attackers could not obtain access to the user accounts. Another test done by the User Experience Questionnaire (UEQ) method found the score on the Pragmatic aspect was 1.927 (Excellent), on the Hedonic aspect it was 1.667 (Excellent), and overall was 1.797 (Excellent).